2006
DOI: 10.1038/nmat1666
|View full text |Cite
|
Sign up to set email alerts
|

Solvent control of crack dynamics in a reversible hydrogel

Abstract: 1The resistance to fracture of reversible biopolymer hydrogels is an important control factor of the cutting/slicing and eating characteristics of food gels 1 . It is also critical for their utilization in tissue engineering, for which mechanical protection of encapsulated components is needed 2,3 . Its dependence on loading rate 4 and, recently, on the density and strength of cross-links 3 has been investigated.But no attention was paid so far to solvent nor to environment effects. Here we report a systematic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(221 citation statements)
references
References 27 publications
(38 reference statements)
11
208
0
Order By: Relevance
“…For gelatin gels, this process occurs without any scission of the polymer chains, but via their stress-induced disentanglement and pull-out [16,17]. Fig.2 displays the stress relaxation curves of the two gels, the compositions of which was chosen so that they exhibit the largest viscosity contrast (η 60 /η 0 = 11, see inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For gelatin gels, this process occurs without any scission of the polymer chains, but via their stress-induced disentanglement and pull-out [16,17]. Fig.2 displays the stress relaxation curves of the two gels, the compositions of which was chosen so that they exhibit the largest viscosity contrast (η 60 /η 0 = 11, see inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After an initial transient, the crack reaches a steady regime at a velocity V which increases with the "energy release rate" G imposed by the opening ∆. We found that, in this slow, subsonic regime (V < 30 mm/s):with G 0 ≃ 2.5 J.m −2 , Γ ≃ 10 6 , and were able to assign this strong V -dependence to the fact that, in such a reversible gel, fracture occurs via scissionless chain pull-out, the high dissipation being due to viscous drag [10,11]. The results reported here were obtained on gels with a 5 wt.% content of gelatin in the solvent (pure water except when otherwise specified).…”
mentioning
confidence: 76%
“…The stress-stretch curve of a hydrogel or an elastomer often depends on loading history due to various inelastic processes such as the Mullins effect [37,38], viscoelasticity [39][40][41][42][43], poroelasticity [42][43][44][45][46] and viscoplasticity [47]. In particular, the Mullins effect has been considered as the major factor to explain the softening of double network hydrogels over consecutive loading cycles [48][49][50][51][52][53][54], and has been attributed to progressive damage of the polymer networks [50,55].…”
Section: Shakedown After Prolonged Cyclingmentioning
confidence: 99%